Integrating Generative Artificial Intelligence (AI)-Based Multimodal Learning in Education to Enhance Literacy Aligned with Sustainable Development Goals (SDGs) - Nurjamin, Asep; Nurjamin, Lucky Rahayu; Fajriah, Yustika Nur; Nurjamin, Aisyah Khoerunnisa; Firdaus, Hijrin Ahmad (Bumi Publikasi Nusantara, 2026)
This study aimed to investigate the integration of artificial intelligence (AI)-based multimodal learning in education to enhance students’ literacy in alignment with Sustainable Development Goals. A quasi-experimental design was employed with elementary students who participated in lessons supported by teacher modelling and AI scaffolding. The intervention was implemented through literacy tasks focusing on descriptive writing and multimodal expression. The results indicated that students improved in their ability to construct coherent descriptive texts enriched with visual elements, demonstrating progress in vocabulary use and multimodal literacy. These findings are significant because the combination of teacher guidance and AI feedback strengthened the learning process by connecting linguistic concepts with meaningful tasks. The study highlights the impact of aligning educational innovations with Sustainable Development Goals (SDGs), showing that AI-assisted multimodal learning can foster student-centered pedagogy, improve literacy development, and provide sustainable pathways for integrating digital technologies into education.